Analysis of Top Management Support on the Quality of Accounting Information System and the Impact on the Quality of Accounting Information - Astuti, Wati Aris; Wulandari, Ajeng Retno (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2023)
Top management support in the accounting information system is one of the factors influencing the quality of the accounting information system. Top management involvement is essential to the success of an organization’s accounting information system. The fundamental role of accounting information systems in an organization is to produce quality accounting information. A quality accounting information system is able to get value to the organization by providing accurate and timely information. Quality information is useful to assist information users in making useful decisions.The purpose of this study was to determine the relationship between top management support on the quality of the accounting information system and its impact on the quality of accounting information at BUMN Majalengka Regency. The method used in this is descriptive verification with a quantitative approach. Test analysis using Path Analysis using SPSS v25 software. The results of this study indicate that top management support has a significant influence on the quality of accounting information systems and the quality of accounting information systems affects the quality of accounting information.